Caracterização do mecanismo de ação relaxante do alcaloide isoquinolínico 1-(3-metoxi-4-hidroxifenil)-7-metoxi-1,2,3,4-tetrahidroisoquilina (MTHP) em aorta isolada de rato - Travassos, Rafael de Almeida (2015)
Natural products are a rich source of compounds for the discovery of new drugs. The importance of these natural products in the discovery and inspiration drug is proven and their synthesis is of significant interest. The isoquinoline alkaloids are commonly found in a variety of natural products and biologically active compounds. The novel synthetic isoquinoline alkaloid, 1- (3-methoxy-4-hydroxyphenyl) -7-methoxy-1,2,3,4- tetrahydroisoquinoline (MTHP), showed relaxing activity on the superior mesenteric artery of normotensive rats by the NO-cGMP pathway. The aim of this study was to investigate the vasorelaxant action mechanism of MTHP in rat aorta. Isometric contractions were monitored, and relative potency and efficacy parameters were determined from cumulative concentration-response curves. The MTHP relaxed significantly and concentration-dependent manner the rings of aorta precontracted with phenylephrine in the presence (EC50 = 2.7 ± 0.2 x 10-6 M) and absence (EC50 = 5.7 ± 1.1 x 10-5 M) of a functional endothelium, being 21 times more potent in the presence of endothelium. In the presence of L-NAME, ODQ and indomethacin, the relaxing potency of MTHP was decreased at 17, 24 and 36 times, respectively. These results suggest the involvement of EDRF in alkaloid mechanism of action. However, in the presence of atropine, non-selective antagonist of muscarinic receptors, the relaxing potency of MTHP is not changed, discarding the involvement of these receptors. MTHP relaxed the aorta rings precontracted with 30 or 80 mM KCl, 3 times more potent for 30 KCl, suggesting upregulation of K + channels. However, on contractions induced by S-(-)-Bay K8644, an activator of CaV1, MTHP relaxed significantly and concentration-dependent manner, suggesting a blocking calcium influx through these channels and that locking takes place by antagonism of the non-competitive type. In the presence of glibenclamide and 4-AP, the relaxing potency of MTHP is not changed, discarding KATP and KV in MTHP mechanism. However, in the presence of 1 mM TEA+ , apamin and BaCl2, its potency was decreased about 12, 13 and 74 times, respectively, suggesting the involvement of BKCa, SKCa and Kir on the vasorelaxant action mechanism of MTHP. In the presence of Y-27632, an inhibitor of ROCK, the relaxing potency of MTHP not changed, discarding the participation of the RhoA/ROCK pathway. MTHP does not interfere with cell viability and apoptosis in rat aorta calls labeled annexin-V and propidium iodide. The MTHP decreased fluorescence induced by 300 mM KCl in myocytes loaded with Fluo-3 and inhibited Ba2+ currents through CaV. These results suggest that MTHP promotes vasorelaxation via EDRF by a upregulation of NOS and cyclooxygenase, as well as activation of soluble guanylyl cyclase (GCs). Furthermore, the alkaloid decreases calcium influx by blocking a direct CaV-L, as well as by positive modulation of SKCa, BKCa and Kir channels. All these events lead to a reduction of [Ca2+]i and consequent relaxation of vascular smooth muscle.